Análise da efetividade dos gastos com educação nos municípios do Estado do Ceará - Cavalcante, Anderson Martins (2018)
This study aimed to analyze how the resources invested in education by the municipalities of the State of Ceará are related to the quality of education provided, measured in terms of performance in IDEB, Promotion, Retention, Evasion and Age-Series Distortion rates. For this, a balanced panel data model was used with the 184 municipalities of Ceará between 2007 and 2013. The results suggest that spending on education in basic education is positively related to the educational quality, both by an increase in performance and by the greater regularity of school flow.